2003
DOI: 10.1093/nar/gng055
|View full text |Cite
|
Sign up to set email alerts
|

A new and versatile method for the successful conversion of AFLPTM markers into simple single locus markers

Abstract: Genetic markers can efficiently be obtained by using amplified fragment length polymorphism (AFLP) fingerprinting because no prior information on DNA sequence is required. However, the conversion of AFLP markers from complex fingerprints into simple single locus assays is perceived as problematic because DNA sequence information is required for the design of new locus-specific PCR primers. In addition, single locus polymorphism (SNP) information is required to design an allele-specific assay. This paper descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 19 publications
1
60
0
Order By: Relevance
“…Our success rate (1 out of 28) for converting an AFLP marker into a SCAR marker falls in the range of the success rates reported in previous studies in salmonids-one out of 15 reported by Felip et al (2005) and one out of 52 reported by Brunelli and Thorgaard (2004). We posit that it might be possible to convert some of the other 27 sex-specific AFLP bands into SCAR markers by using genome walking to reveal the sequences spanning the regions outside the AFLP marker, as was carried out for the male-sterility marker in the plant Brassica napus (Zeng et al, 2009) and in potato; in the latter study, genome walking facilitated the successful conversion of six of 10 AFLP markers to SCAR markers (Brugmans et al, 2003). Genome walking was necessary in the above six instances owing to the fact that the single-nucleotide polymorphisms (SNPs) resided in the restriction site.…”
Section: Resultsmentioning
confidence: 94%
“…Our success rate (1 out of 28) for converting an AFLP marker into a SCAR marker falls in the range of the success rates reported in previous studies in salmonids-one out of 15 reported by Felip et al (2005) and one out of 52 reported by Brunelli and Thorgaard (2004). We posit that it might be possible to convert some of the other 27 sex-specific AFLP bands into SCAR markers by using genome walking to reveal the sequences spanning the regions outside the AFLP marker, as was carried out for the male-sterility marker in the plant Brassica napus (Zeng et al, 2009) and in potato; in the latter study, genome walking facilitated the successful conversion of six of 10 AFLP markers to SCAR markers (Brugmans et al, 2003). Genome walking was necessary in the above six instances owing to the fact that the single-nucleotide polymorphisms (SNPs) resided in the restriction site.…”
Section: Resultsmentioning
confidence: 94%
“…The original AFLP fingerprint including the AFLP fragment that highly differentiated between Sumatra and Borneo had been generated with the selective primer pair E35/M63 with the three selective nucleotides ACA and GAA, respectively (Cao et al 2006). To increase the probability of successful excision of the desired fragments from the gel, an additional nucleotide (A, T, C, G) was added to the selective M primer (Brugmans et al 2003;Gailing and Bachmann 2003). Two different selective amplifications were prepared: (1) using the MseI+4 primer and EcoRI primer labeled with the fluorescent dye Cy-5 for gel-extraction from a 7% polyacrylamide (PAA) gel and (2) using the MseI+4 primer and EcoRI primer labeled with the fluorescent dye 6-FAM for comparison with the original AFLP fingerprint after capillary electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…The selective amplification using the MseI primers elongated by one base reduced the number of fragments and prevented co-isolation of contaminating DNA fragments (see also Brugmans et al 2003;Gailing and Bachmann 2003). Thus, this protocol facilitates the excision of the target band from the gel.…”
Section: Isolation and Sequencing Of The Aflp-172 Fragmentmentioning
confidence: 99%
See 2 more Smart Citations